Pengaruh Car, Suku Bunga, Nilai Tukar Valas, Jumlah Uang Beredar, Tingkat Resiko Pembiayaan Musyarakah Dan Mudharabah Terhadap Profitabilitas Bank Syariah (Pada Bank Umum Syariah di Indonesia Periode 2011-2015) - Binugrahini, Dinar (2017)
Abstract The study aims to analyze the effect of the Capital Adequacy Ratio (CAR), Interest Rates, Foreign Exchange Rates, Money Supply, Musyarakah Financing Risk and Mudharabah Financing Risk to Profitability the Islamic Banking. Population as an object of the research is Islamic Commercial Bank Listed on Bank Indonesia (BI) of the period 2011-2015. The number of samples used ware 8 Islamic Commercial Bank Listed on Bank Indonesia. The sampling technique used was purposive sampling with the certain criteria which the Islamic Commercial Bank Listed on Bank Indonesia of the period 2011-2015, the Islamic Commercial Bank that publish annual report on their websites, and the Islamic Commercial Bank that has a complete data based on variables studied. The analysis technique used is the multiple regression analysis and hypothesis test with a level of significance of 5%. Before using multiple regression analysis, performed classical assumption first. From the results of simultaneous hypothesis test (F test) showed that the CAR, Interest Rates, Foreign Exchange Rates, Money Supply, Musyarakah Financing Risk and Mudharabah Financing Risk has a significant impact on Profitability of Islamic Banking with a significance lavel of 0,000. While based on the partial results of hypothesis testing (t test) showed that the CAR and Mudharabah Financial Risk has a significant effect on profitability of Islamic Banking. While the Interest Rates, Foreign Exchange Rates, Money Supply, and Musyarakah Financing Riskis not significant effect on profitability of Islamic Banking. Thevalue of adjusted R2 in regression model obtained 0,428. This shows that the major effect of independent variables to dependent variables of 42,8%, while the remaining 57,2% is influenced by other factors. Keywords: CAR, Interest Rates, Foreign Exchange Rates, Money Supply, Musyarakah Financing Risk, Mudharabah Financing Risk, Profitability